PENERAPAN FUZZY DATABASE TAHANI PADA APLIKASI PEREKRUTAN KARYAWAN - Budi Wasito; Hartawan Budiman (Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
PT XYZ is a company that provides consulting services, software, and hardware. In conducting its business PT XYZ requires human resources. The existence of human resources needs to make PT XYZ need to recruit employees. Currently, PT XYZ still uses a manual system in its recruitment process starting from the candidate selection process of employee, recording progress of candidate of the employee, process of data archiving of the candidate, until notification to parties related to the recruitment process. The absence of integration of employee candidate data files between recruiters causes refractions of each recruiter to be limited only to the recruiter candidate's data re-fertion. Psychotest process that is applied also still use application-based desktop application. This leads to a psychotest stage for an employee candidate who is outside the city to be performed by the service bureau. Keywords: Recruitment, Fuzzy Tahani, laravel